2016
DOI: 10.1016/j.jnucmat.2016.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, concentration, and uranium chloride mixture on zirconium electrochemical studies in LiCl KCl eutectic salt

Abstract: Experimental studies were performed to provide measurement and analysis of zirconium (Zr) electrochemistry in LiCl-KCl eutectic salt at different temperatures and concentrations using cyclic voltammetry (CV). An additional experimental set with uranium chloride added into the system forming UCl 3-ZrCl 4-LiCl-KCl was performed to explore the general behavior of these two species together. Results of CV experiments with ZrCl 4 show complicated cathodic and anodic peaks, which were identified along with the Zr re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…However, after long-term service of the cladding material, the fission product will penetrate into cladding materials, causing the Zr alloys to lose excellent properties . It is reported that the contaminated Zr alloys account for more than 40% of spent fuels assembly volume, and the content of Zr could reach 10.8 wt % in the irradiated driving fuel. , Thus, recovering Zr from contaminated Zr alloys and spent fuels not only reduce the volume of radioactive waste but also brings economic benefits to the nuclear power industry. In recent decades, this has always been a hot issue in the nuclear field.…”
Section: Introductionmentioning
confidence: 99%
“…However, after long-term service of the cladding material, the fission product will penetrate into cladding materials, causing the Zr alloys to lose excellent properties . It is reported that the contaminated Zr alloys account for more than 40% of spent fuels assembly volume, and the content of Zr could reach 10.8 wt % in the irradiated driving fuel. , Thus, recovering Zr from contaminated Zr alloys and spent fuels not only reduce the volume of radioactive waste but also brings economic benefits to the nuclear power industry. In recent decades, this has always been a hot issue in the nuclear field.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as temperature, concentration of zirconium, salt composition have been considered. In chloride-based salt mixtures such as LiCl-KCl-ZrCl 4 , 2,4,[7][8][9][10][11][12][13][14][15][16][17] NaCl-KCl-ZrCl 4 , 18 NaCl-ZrCl 4 , 8 it was believed that the reduction of Zr(IV) followed a multi-step mechanism, two soluble states of Zr(IV) and Zr(II) and two insoluble states of Zr(I) and Zr were confirmed. In fluoride-based salt mixtures, the reduction was thought to be less complicated, a single-step reduction of Zr(IV) to Zr(0) was approved in LiF-NaF-ZrF 4 , 19 LiF-CaF 2 -ZrF 4 , 20 and LiF-KF-ZrF 4 , 21 and a two-step reduction was endorsed in LiF-NaF-K 2 ZrF 6 , 22 LiF-KF-ZrF 4 .…”
mentioning
confidence: 99%
“…To overcome the shortcoming of volatilization of AlCl 3 , it is worth considering in future work to control the amount of dissolved AlCl 3 in LiCl−KCl salts through appropriate preparation steps by adopting the method developed by Hoover et al The amount of dissolved U 3 O 8 and UO 3 can be more accurately monitored. 35 Although the measurement results deviate from the true value, the overall trend of the U dissolution process reflected by the results of ICP-OES should be acceptable. Moreover, it can also be seen that the molten salt becomes viscous in Figure 3b after the dissolution of U 3 O 8 for 5 h. Whereas, according to Figure 3c,d, the bright yellow of the molten salt was obviously observed, which reveals that the dissolved product of UO 3 in the molten salt may be different from U 3 O 8 .…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…In addition, the volatilization phenomenon of AlCl 3 in the molten salt is more obvious with the increase of its content during the dissolution of uranium oxides, which may be the main reason for the measurement errors of the U ion concentration. To overcome the shortcoming of volatilization of AlCl 3 , it is worth considering in future work to control the amount of dissolved AlCl 3 in LiCl–KCl salts through appropriate preparation steps by adopting the method developed by Hoover et al The amount of dissolved U 3 O 8 and UO 3 can be more accurately monitored . Although the measurement results deviate from the true value, the overall trend of the U dissolution process reflected by the results of ICP-OES should be acceptable.…”
Section: Resultsmentioning
confidence: 99%